Friendly Frenzy - Arnold, Tedd (New York : Cartwheel Books, an imprint of Scholastic Inc., 2021)
Buzz, Fly Guy, Liz, and Fly Girl meet a boy a named Carlos in the park, but Carlos has a pet lizard with a taste for flies--so it looks like this is a friendship that is doomed from the start.
Ages 4-8.
Grades K-1.
Keywords: Flies -- Juvenile fiction; Lizards -- Juvenile fiction; Friendship -- Juvenile fiction; Flies -- Fiction; Lizards -- Fiction; Friendship -- Fiction; Humorous fiction